2008
DOI: 10.1038/sj.bjc.6604249
|View full text |Cite
|
Sign up to set email alerts
|

Multicentre prospective phase II trial of gefitinib for advanced non-small cell lung cancer with epidermal growth factor receptor mutations: results of the West Japan Thoracic Oncology Group trial (WJTOG0403)

Abstract: The purpose of this study was to evaluate the efficacy of gefitinib and the feasibility of screening for epidermal growth factor receptor (EGFR) mutations among select patients with advanced non-small cell lung cancer (NSCLC). Stage IIIB/IV NSCLC, chemotherapynaive patients or patients with recurrences after up to two prior chemotherapy regimens were eligible. Direct sequencing using DNA from tumour specimens was performed by a central laboratory to detect EGFR mutations. Patients harbouring EGFR mutations rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
106
1
5

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(117 citation statements)
references
References 35 publications
(41 reference statements)
5
106
1
5
Order By: Relevance
“…Thirty-three patients with advanced or recurrent non-adenocarcinoma NSCLC who had the somatic EGFR mutations and were treated with gefitinib were selected from 15 reports. (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31) Table 1 summarizes the 15 identified clinical reports. The 15 reports included five prospective studies and 10 retrospective studies including four studies using the data of expanded access programs of gefitinib.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirty-three patients with advanced or recurrent non-adenocarcinoma NSCLC who had the somatic EGFR mutations and were treated with gefitinib were selected from 15 reports. (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31) Table 1 summarizes the 15 identified clinical reports. The 15 reports included five prospective studies and 10 retrospective studies including four studies using the data of expanded access programs of gefitinib.…”
Section: Resultsmentioning
confidence: 99%
“…(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31) The study included any reports based on the method of DNA isolation from fresh tissue or paraffin-embedded tissue, and the technique used to enhance tumor-derived DNA, which included either microdissection or use of the more sensitive polymerase chain reaction (PCR) amplification techniques. Not all consecutive NSCLC patients were included in the EGFR mutation analysis in every study.…”
Section: Methodsmentioning
confidence: 99%
“…13,[17][18][19][20][21] The incidence of EGFR mutations in unselected tumors with non-small cell histology ranges from 10 to 50%, depending upon the ethnic makeup of the patient population and the detection methods used for mutation analysis; 95% of such mutations have been found in adenocarcinomas. 12,13,16,[22][23][24][25][26][27][28][29][30][31][32][33][34] Although the exact molecular mechanisms resulting from these somatic mutations are not completely understood, it seems clear that mutant EGFR has enhanced tyrosine kinase activity. Tyrosine kinase is an enzyme that transports phosphates from adenosine triphosphate (ATP) to a protein's tyrosine residue.…”
mentioning
confidence: 99%
“…(10)(11)(12)(13)(14) Indeed, we and others have prospectively demonstrated a high response rate to EGFR TKI therapy in NSCLC patients with EGFR mutations. (15)(16)(17)(18)(19)(20)(21) An increased copy number of the EGFR gene, as revealed by fluorescence in situ hybridization (FISH), has also emerged as an effective molecular marker of EGFR TKI sensitivity in NSCLC. (22)(23)(24) We previously showed that EGFR mutation and EGFR amplification are associated in human NSCLC cell lines and that endogenous EGFR expressed in such cell lines positive for both of these EGFR alterations are activated constitutively.…”
mentioning
confidence: 99%